Student perceptions: Background to a new ethics curriculum in Indian medical colleges - Shimpa Sharma; Rakesh Sharma; Rajesh K Khyalappa; Shweta Sharma; Samin Kandoth (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Ethic education as a part of medical school curriculum is one which requires constant re-evaluation and re-emphasis. The medical regulatory body of India has, in recent times, introduced a revised module of the same, which is implemented across the country in all medical schools. Medical students' perception of ethics education is an important variable which will influence the validity of this module. This study attempts to evaluate the same. MATERIALS AND METHODS: A peer-validated questionnaire was distributed to 150 undergraduate and postgraduate medical students (response rate: 74.4%) with the aim to evaluate their attitude toward knowledge of ethics, and their perceptions of contents and methods of learning ethics. RESULTS: A significant number of students recognize the importance of medical ethics knowledge and its positive impact on their career (P < 0.05). They accept material taught as per planned curriculum as a source of learning and favor interactive methods of teaching (P < 0.05). Research projects and didactic lectures were rejected as learning methods (P < 0.05). CONCLUSION: "Deliberate teaching" has been accepted as a source of learning ethics by all students, though undergraduate students also favored learning about ethics "during practice." Perceptions have been identified that need to be addressed. The study reveals a need to further explore the purpose and contribution of role models in this context and to identify ways of strengthening their related perceptions by students.